A Domino Approach for the Synthesis of α, β‐Epoxy Ketones from Carbonyl Compounds under Neat Conditions at Ambient Temperature. Issue 26 (10th July 2018) - Mahato, Sachinta; Santra, Sougata; De, Aramita; Chatterjee, Rana; Zyryanov, Grigory V.; Majee, Adinath
Abstract: An efficient method has been developed for the synthesis of α, β‐epoxy ketones from one pot reaction between aldehydes and ketones in presence of cesium carbonate and tert ‐butyl hydrogen peroxide (TBHP) under neat conditions. In this methodology we have used the one pot domino type reaction with aldehydes and ketones to get α, β‐epoxy ketones without presynthesized chalcone precursors. A library of α, β‐epoxy ketones having a variety of substituents has been synthesized. Clean reaction, mild reaction conditions, ease of product isolation/purification, easily accessible reactants, wide substrates scope and metal and solvent‐free and environmental friendly reaction conditions are the notable advantages of the present method. The present methodology is applicable to gram scale synthesis. Abstract : An efficient method has been reported for the synthesis of α, β‐epoxy ketones from one pot reaction between aldehydes and ketones in presence of cesium carbonate and tert ‐butyl hydrogen peroxide (TBHP) under neat conditions. In our methodology we have used the one‐pot domino type reaction with aldehydes and ketones to get α, β‐epoxy ketones without presynthesizing the chalcone precursors. No external solvent was needed to carry out the reaction. Cesium carbonate was found to be the effective base for this reaction.